2006
DOI: 10.1093/ndt/gfl169
|View full text |Cite
|
Sign up to set email alerts
|

Positive effect of dietary soy in ESRD patients with systemic inflammation—correlation between blood levels of the soy isoflavones and the acute-phase reactants

Abstract: These data suggest the possibility of beneficial effects of isoflavone-rich soy foods on the inflammatory and nutritional status of HD patients with underlying systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 18 publications
4
96
1
2
Order By: Relevance
“…In addition, an anti-inflammatory and nutritional effect has also been observed in patients with end-stage renal disease that received isoflavone-containing soy-based nutritional supplements (7). In this regard, we have also previously shown that the progression rate to renal injury in obese Zucker rats was decreased by consumption of a soy protein diet (39).…”
Section: Discussionmentioning
confidence: 82%
“…In addition, an anti-inflammatory and nutritional effect has also been observed in patients with end-stage renal disease that received isoflavone-containing soy-based nutritional supplements (7). In this regard, we have also previously shown that the progression rate to renal injury in obese Zucker rats was decreased by consumption of a soy protein diet (39).…”
Section: Discussionmentioning
confidence: 82%
“…Increases in total isoflavones, genistein and daidzein (59) and genistein levels (63) induced by long-term soya consumption were not associated with CRP reductions (59,63) . When pure molecules were utilized, CRP and IL-8 were lowered by quercetin supplementation in runners (64) and bikers (65) , while quercetin plasma levels increased.…”
Section: Anti-inflammatory Properties Of Flavonoidsmentioning
confidence: 76%
“…Long-term intervention studies conducted using soya as a source of bioactive molecules showed reduction in levels of vascular cell adhesion molecule-1 and CRP (59,60) , but also a lack of effect on CRP (61)(62)(63) , TNFa (61,63) and IL-6 (60,62) . Increases in total isoflavones, genistein and daidzein (59) and genistein levels (63) induced by long-term soya consumption were not associated with CRP reductions (59,63) .…”
Section: Anti-inflammatory Properties Of Flavonoidsmentioning
confidence: 99%
“…Hemodiyaliz tedavisi alan ve CRP düzeyi yüksek (>10.0 mg/l) olan son evre böbrek yetmezliği hastalarında 8 hafta boyunca soya isoflavonları suplemantasyonu (diyaliz sonrası soya bazlı içecek (54 mg isoflavon) ve diğer günlerde tahıllı ürün (26 mg isoflavon) veya proteinli bar (26 mg isoflavon)) yapılmıştır. Sekiz haftanın sonunda test grubunda kan isoflavon düzeylerinin kontrol grubuna göre 5-10 kat daha yüksek olduğu ve CRP düzeyinin başlangıca oranla daha düşük olduğu gösterilmiştir (87).…”
Section: Flavonoidlerunclassified